Pengaruh Literasi Keuangan, dan Financial Technology terhadap Keputusan Keuangan Mahasiswa Yogyakarta - Ismi Solikhatun; Ahmad Ajib Ridlwan (Edunusa: Journal of Economics and Business Education, 2022)
This study aims to 1) determine the effect of financial literacy on the financial decisions of Yogyakarta students, 2) determine the effect of financial technology (fintech) on the financial decisions of Yogyakarta students, 3) determine the effect of financial literacy and the use of financial technology (fintech) together on decisions. Yogyakarta student finance. This research is an ex post facto type of research with the approach used is a quantitative approach. The population in this study was students in Yogyakarta. This research will use a proportional random sampling technique with a sample of 65 students from 10 universities in Yogyakarta. Financial literacy has a financial literacy variable that has a positive effect on student financial decisions in Yogyakarta. The use of fintech does not affect the financial decisions of students in Yogyakarta. Seeing the positive influence of understanding financial literacy on financial decision-making, including in terms of savings and investment, financial literacy needs to be given to the community and students in general and the people of Yogyakarta in particular.